2018
DOI: 10.1055/s-0038-1646927
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Acetaminophen May Be Associated with Reduced Odds of 30-Day Readmission after Total Knee Arthroplasty

Abstract: The purpose of this study was (1) to evaluate 30-day readmission rates in total knee arthroplasty (TKA) patients who either received intravenous (IV) or oral (PO) acetaminophen (APAP) perioperatively and (2) to extrapolate the potential annual cost savings on the national level. This was a review of 190,691 TKA recipients between the years 2012 and 2015 who received either IV ( = 56,475) or PO APAP ( = 134,216). All-cause readmissions that occurred between patient discharge and 30 days postdischarge were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Acetaminophen, as an analgesic, is often used to assist the analgesic effect of other drugs. Murata-ooiwa M et al [ 18 ] and Mont Ma et al [ 39 ] both confirmed the effect of acetaminophen on the pain management after TKA surgeryin achieving effective pain control for the patients. Mont Ma et al [ 39 ] had also confirmed that the use of acetaminophen could reduce the probability of reoperation and save the cost of patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Acetaminophen, as an analgesic, is often used to assist the analgesic effect of other drugs. Murata-ooiwa M et al [ 18 ] and Mont Ma et al [ 39 ] both confirmed the effect of acetaminophen on the pain management after TKA surgeryin achieving effective pain control for the patients. Mont Ma et al [ 39 ] had also confirmed that the use of acetaminophen could reduce the probability of reoperation and save the cost of patients.…”
Section: Discussionmentioning
confidence: 87%
“…Other types of analgesics, such as pregabalin was also used by the patients in this study. Some research results showed that while this other type of analgesics such as gabapentin and pregabalin could alleviate postoperative pain and reduce the use of opioids [ 39 , 40 ], the adverse reactions and effectiveness of the drugs have yet to be confirmed [ 41 , 42 , 43 , 44 ]. How to avoid adverse reactions of analgesics in TKA needs more clinical research.…”
Section: Discussionmentioning
confidence: 99%
“… 44 IV acetaminophen reduced the likelihood of readmission after 30 days following knee arthroscopy. 45 This raises the possibility that the actions of acetaminophen reflect disease modifying actions that alter the transition from an acute to a chronic pain state hypothesized to reflect a role of innate/adaptive immune systems. 46 Less promising results have also been reported, 47 concerns of toxicity remain 48 and the superiority of IV vs PO acetaminophen has been questioned.…”
Section: Analgesic Efficacy Of Acetaminophen In Humansmentioning
confidence: 99%